Gum and resin bearing dryland forests of Somali region, Southeastern Ethiopia: Diversity, structure and spatial distribution - Yahya, Nesibu; Abdelkadir, Abdu; Teshome, Busha; Abebe, Mister; Kassa, Habtemariam (International Journal of Agricultural Research, Innovation and Technology, 2024)
Despite its ecological and socio-economic contributions, the lowland dry forests of Ethiopia have been experiencing severe deforestation and degradation challenges. It is, therefore, crucial to assess the status of the dry forest resources to formulate an appropriate management strategy and its sustainable utilization. This study was formulated to determine spatial distribution, species composition, structure, and regeneration of the gum and resin species bearing dry forests in the Somali regional state of Ethiopia. The recent Sentinel-2A image was procured and used to classify the area, using a supervised Random Forest Algorithm, into different land covers and vegetation types. Inside the two key vegetation types (Acacia dominated woodland and Mixed woodland), forest inventory was conducted by establishing 30 m x 30 m size quadratic sample plots. The results revealed that the study area was divided into settlement (0.2%), bare land (6.0%), undifferentiated forest (0.5%), acacia woodland (36.3%), mixed woodland (54.1%) and scrubland (2.9%). Thirty-four woody species were identified and recorded with a Shannon diversity of 3.03. The population structure showed a lack of sufficient natural regeneration. It is, therefore, imperative to say that the forest containing the gum and resin-bearing species is not replacing itself. On the other hand, the forest has the potential to produce Oleo-gum resin in various kinds and amounts. Thus, implementing appropriate restoration measures is urgent to enhance natural regeneration. Moreover, formulating sustainable utilization while creating product market of gum and resins are important considerations for the future development of the sector. Int. J. Agril. Res. Innov. Tech. 13(2): 6-13, Dec 2023